Eksistensi Pondok Pesantren dalam Memperkuat Literasi Islam di Era Globalisasi - Mas’ud, Moh. Ali (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2019)
The role of Islamic Boarding Schools from hereditary in maintaining and strengthening Islamic literacy and building national moderation is very large and undoubted. It is evident from the existence of pesantren graduates who are easily accepted in the midst of society (Out Coming), and many Islamic boarding school alumni become determinants and changes to the real conditions of society, both in the order of worship, mua'amalah, aqidah, and other living rules. In addition, religious leaders currently including graduates of Islamic boarding schools have started to openly participate in filling the seat of government, this is an advantage and progress in how the figure of santri with good aqeedah and personal resilience from various frictions is also a determinant of government policy when senior politicians were busy taking care of various cases that happened to him.